The REFLECT design-flow - Cardoso,JMP; José,JG; Nane,R; Sima,VM; Olivier,B; Carvalho,T; Nobre,R; Diniz,PC; Petrov,Z; Bertels,K; Gonçalves,F; Van,Someren H; et al. (2013)
This chapter describes the design-flow approach developed in the REFLECT project as presented originally in [1]. Over the course of the project, this design-flow has evolved and has been extended into a fully operational toolchain. We begin by presenting an overview of the underlying aspect-oriented compilation flow followed by an extended description of the design-flow and its toolchain.